DIGITAL DICTIONARY ENTRIES AND THEIR MAIN COMPONENTS - Sulaymonov Bobir (International Journal of Literature and Language Studies, 2026)
This article examines the structure and development of digital lexicography in contemporary world linguistics, focusing on the dictionary entry as the core microstructural unit of electronic dictionaries. It explores how traditional lexicographic principles are integrated with information and communication technologies, including artificial intelligence, corpus linguistics, and NLP tools. Special attention is given to the components of digital dictionary entries such as pronunciation, grammatical labels, semantic information, collocations, multimedia elements, and hypertext features. The study also analyzes major international dictionary platforms (Oxford, Cambridge, Merriam-Webster, Collins, and Longman) and highlights the growing role of mobile applications and machine translation systems in modern lexicography. Finally, the article discusses the implications of digital lexicography for Uzbek lexicographic studies, emphasizing issues of microstructure optimization, user experience, and information accessibility.